The implementation of a toy-based program for children to enhance their problem-solving skills in the Philippine toy library - Pascua, Vinny Andrew B.; Silverio, Rochelle S. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2016)
This research sought to determine whether toy-based programs can improve the problem-solving skills of children. The experimental study was conducted at the Philippine Toy Library at Loyola Heights, Quezon City. Five preschoolers underwent a toy-based program which aims to enhance their logic reasoning, memory, and creativity. It ran for five weeks. There were two sessions per week and each session lasted for 30 minutes. A pretest and post-test was done to measure any development. The researcher also conducted a survey to know the perception of the respondents and actual children visitors towards the Philippine Toy Library and their insights on the implementation of toy-based programs.
Results showed that: (1) the toy-based program ca successfully improve the children's problem-solving skills particularly on logic reasoning and creativity; (2) toy-based programs help toy libraries motivate young children to visit the library more; and (3) young children's perception of the Philippine Toy Library is generally positive. Provision of more toys, maintenance of existing toys, conduct of toy-based programs, and opening on Saturdays are recommended to the Philippine Toy Library. Suggestion for further studies include the (1) implementation of toy-based programs that can develop other thinking skills for children and (2) running toy-based programs on different age levels.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Toy lending libraries -- Philippines -- Quezon City; Children's libraries -- Activity programs -- Philippines -- Quezon City